Do Cleft Lip and Palate Types Affect Health-Related Quality of Life of Adolescents?. Issue 3 (May 2019) - Crepaldi, Thainara Alves; Vitor, Luciana Lourenço Ribeiro; Carrara, Cleide Felicio Carvalho; Rios, Daniela; Cruvinel, Thiago; Almeida, Ana Lúcia Pompéia Fraga; Soares, Simone; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract : Abstract: The adolescent with oral cleft must deal with the process of body changing and the psychological implications caused by morphological, functional, and esthetic impairments of the cleft itself. This study aimed to evaluate whether the cleft lip and palate types affects health-related quality of life of adolescents through Short-form Health Survey (SF-36) questionnaire. Fifty-seven adolescents (29 males and 28 females; mean age 15 years and 11 months ± 1 year and 2 months) were divided into 2 groups: Group 1—single cleft—unilateral or bilateral CL or CP; Group 2—complex cleft—unilateral or bilateral cleft lip and palate. The participants filled in SF-36 questionnaire to verify their functional, physical, and mental well-being profile. Spearman test assessed SF-36 scores correlation with age. Mann–Whitney U test verified the differences between genders and cleft types. Linear regression models were used to analyze confounding factors (age and gender). P was set at <0.05. The different SF-36 domains weakly correlated with age, ranging from −0.07 ( P = 0.60) for the social aspects and 0.31 ( P = 0.02) for general health. Females had statistically lower SF-36 scores than males in the domains Bodily pain ( P = 0.02), Vitality ( P < 0.001), and Mental Health ( P < 0.001). G1 showed lower scores in the domains Limitations due to Emotional Problems ( P = 0.008) and Mental Health ( P = 0.036). However, when the confounding factors (age and gender) were analyzed, the oral cleft type did not affect health-related quality of life ( P > 0.05). Considering the age and gender, the cleft lip and palate types did not affect the health-related quality of life of adolescents.